A Spectrophotometric Assay for Robust Viability Testing of Seed Batches Using 2,3,5-Triphenyl Tetrazolium Chloride: Using Hordeum vulgare L. as a Model - Lopez Del Egido, Laura; Navarro-Miró, David; Martinez-Heredia, Victor; Toorop, Peter E.; Iannetta, Pietro P. M. (Frontiers in Plant Science, 2017)
A comparative analysis was carried out of published methods to assess seed viability using 2,3,5-triphenyltetrazolium chloride (TTC) based assays of seed batches. The tests were carried out on seeds of barley (Hordeum vulgare cv. Optic) as a model. We established that 10% [w/v] trichloroacetic acid (TCA)/methanol is superior to the acetone and methanol-only based methods: allowing the highest recovery of formazan and the lowest background optical density (OD) readings, across seed lots comprising different ratios of viable and dead seeds. The method allowed a linear-model to accurately capture the statistically significant relationship between the quantity of formazan that could be extracted using the method we developed and the seed temperature-response, and seed viability as a function of artificially aged seed lots. Other quality control steps are defined to help ensure the assay is robust and these are reported in a Standard Operating Procedure.